Factors Influencing the Profitability of Non-Life Insurance Companies in Nepal: An Empirical Analysis - Karki, Nishant (Apex Journal of Business and Management, 2025)
This study investigates the factors influencing the profitability of non-life insurance companies in Nepal, focusing on the impact of company age, leverage, liquidity, and size. A quantitative research methodology is used, employing descriptive and correlational research designs. Secondary data from seven non-life insurance companies in Nepal from 2014 to 2023, totaling 70 observations, were analyzed. The dependent variables—Return on Assets (ROA) and Return on Equity (ROE)—are examined in relation to the independent variables. Data were sourced from the Nepal Insurance Authority and the companies' websites. Descriptive statistics show that the average ROA is 8.82% and the average ROE is 14.37%. The average values for the independent variables are 24.35 years (age), 63.66% (liquidity), 94.73% (leverage), and 2.07 billion NPR (company size). Correlation and regression analyses reveal that leverage is the most consistent factor influencing profitability. The unit root test confirms the stability of the variables, making the regression model applicable. The Hausman test indicates that the fixed effect model is more suitable for ROA, while the random effect model works better for ROE. The analysis finds that company age negatively impacts ROE, and liquidity shows a negative correlation with both ROA and ROE. However, leverage and company size are positively correlated with profitability.